STEATOCYSTOMA MULTIPLEX IN AN ADOLESCENT BOY: A CASE REPORT - Sotirovski, Tomica; Tusheva, Ivana; Blazheska, Ana; Djambazova, Marija; Peev, Igor; Damevska, Katerina (Faculty of Medicine, Ss. Cyril and Methodius University in Skopje, 2023)
Steatocystoma multiplex (SM) is a rare genodermatosis transmitted as an autosomal dominant trait caused most often by a mutation in the gene coding for keratin 17. There are some sporadic cases described in the literature. The disease commonly manifests as numerous intradermal cysts caused by hamartomatous malformations of the pilosebaceous duct junction. The cysts can be located in any skin region, mainly on the chest. The disease is usually benign and asymptomatic, but it can be exceptionally disfiguring, which is the main reason for a medical visit. Pachyonychia congenita type-2 and the eruptive vellus hair cyst are closely related to SM; therefore, histopathological confirmation is necessary before starting any treatment. Here, we present a case of a widespread SM in an adolescent boy, focusing on its clinical and histopathological characteristics.
Keywords: steatocystoma multiplex; eratin-17; hereditary; cyst; acne; genodermatosis